Effect of organic and mineral fertilizer on the yield of Cauliflower and nutrient content of Nitrogen, Phosphorus and Potassium. - Tajalden, M.M.; Ahmed, F.A.W.; Nayyef, Alaa (2014)
An experiment was conducted in one field of Collage of Agriculture – Baghdad University during 2011 - 2012 growing season in a silty clay loam soil to study the effect of added organic and mineral fertilizers in the yield of Cauliflower cv. Sold snow and concentration of nutrients N, P and K . within randomized complete block design (RCBD) for fertilization following transactions: one level of organic fertilizer 1200 kg. ha-1 using fertilizer (Homobakter A) added before planting mixing with surface soil (0-10 cm) and tow Levels of mineral fertilizers, half recommended levels (120 , 40 , 60 ) Kg N , P , K . ha-1 and complete level (240 , 80 , 120) Kg N , P , K . ha-1 respectively . Results showed a significant increase in the concentration of nutrients NPK in flower tablets of cauliflower plant with organic fertilizer addition as compared to untreated plants the increment were 14.67 , 14.28 and 7.70 % for these nutrients respectively . Also concentrations of N , P and K had been increase as mineral fertilizers in crease by 28.76 , 21.05 and 30.58 % for half recommended fertilizers levels and 40.27 , 31.57 and 41.75 % for complete recommended levels . Yield of flower tablets also increased with organic fertilizer addition by 40.89 % and 57.62 , 97.66 % for half and complete mineral fertilizers addition respectively . The recommendation under the condition of this study was half mineral fertilizers levels can be reduced by organic fertilizers addition.